Behavioral Relationship Life Clean And Healthy On Knowledge Of Hygiene Personal Students Of State Elementary School Of Gowa District, South Sulawesi - Mustarin, Yanti; Pannyiwi, Rahmat; Latif, Sarifudin Andi; Samila, Samila; Sallo, Andi Kamal M. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
In Law Number 36 of 2009 Article 79 concerning health, it is emphasized that